Kuat Tekan Material Dari Bahan Komposit Diperkuat Serat Tandan Kosong Kelapa Sawit (TKKS) - Syukarni Ali; Rusman AR (universitas teuku umar, 2017)
Oil palm empty fruit bunches waste (TKKS) is produced annually around ± 23.3 tons of waste per hectare. Therefore, the need for further utilization of the TKKS utilization for technological products is still very low used. And Economical products that have been done such as particle board manufacturing with phenol formaldehyde adhesive and paper raw materials, Indonesia as an agrarian country with accumulated development outside the average land area of 11.12 per year . Palm production 1.9 million tons of dry weight or 4 million tons of wet weight per year. This study aims to obtain the compressive strength of the material from fiber-reinforced composite TKKS material. From the results of this study will reduce the production of waste TKKS and can be utilized as material that has the value of economical products and high selling power. Method of execution of this research by treating TKKS waste and compressive static test of composite material by using test result of servopulser which has been obtained by average value of Voltage (σ) 65,45 (N / mm2), Strain (ε) 0,073 mm, Modulus of Elasticity (E ) 926.34 (MPa). Keywords : oil palm empty fruit bunch waste, economical products, compressive strenght of the material